The quest to decipher HLA immunogenicity: Telling friend from foe. Issue 10 (8th July 2019) - Tambur, Anat R.; McDowell, Hannah; Hod‐Dvorai, Reut; Abundis, Maria A. C.; Pinelli, David F.
Abstract : Molecular mismatch load analysis was recently introduced as a means for performing risk stratification following organ transplantation. However, although good correlation was demonstrated between molecular mismatch load and generation of de novo donor‐specific HLA antibody (DSA), quite a few exceptions exist, and the underlying factors that define HLA immunogenicity remain unclear. Herein, we present a new paradigm to interrogate differences between molecular mismatches that lead to the generation of de novo DSA and those that do not (the 2MM1DSA cohort). Specifically, patients transplanted across 2 HLA‐DQ mismatches, who formed de novo DSA only to one mismatch (foe) but not the other (friend), provide a unique environment in which patient‐specific factors that affect the immune response other than immunogenicity, such as infection and immunosuppression, can be controlled for. It further permits focusing on mismatches uniquely exhibited by the de novo DSA allele, rather than mismatches shared by both DSA and non‐DSA alleles. This concept paper illustrates several examples, highlights the need for center‐specific or population‐specific cutoff values for posttransplant risk stratification, and mostly argues that if there is no direct correlation between molecular mismatch load and immunogenicity, then molecular mismatch load must not be adopted as an approach for equitable organ allocation . Abstract : The authors propose a new concept to refine the study of immunogenicity, taking advantage of insights learned from individual patients who selectively developed HLA‐DQ antibodies to one donor mismatch but not the other—the 2MM1DSA cohort.